Nutritional composition of anthesising male inflorescence of oil palm Elaeis guineensis essential for development of Elaeidobius kamerunicus Faust: first report - Zulkefli, Muhamad Haziq Hadif; Jamian, Syari; Ismail, Siti Izera; Adam, Nur Azura; Jalinas, Johari; Mohd Masri, Mohamed Mazmira (Lembaga Minyak Sawit Malaysia, 2024)
Rearing of Elaeidobius kamerunicus, the pollinator of oil palm, requires the anthesising male inflorescence of oil palm as the breeding and feeding ground. Various studies have reported on the weevils utilising the male inflorescence as feed to sustain its development. However, for routine rearing, the use of male inflorescence is inconvenient as it has to be continuously collected from the field. Thus, this pioneering study was conducted to determine the nutritional composition of anthesising male inflorescence of oil palm (Elaeis guineensis Jacq.) which is essential for E. kamerunicus life development. First, proximate analysis was performed to determine the nutritional composition of anthesising male inflorescence. Next, the nutritional profiles of amino acids, fatty acids and carbohydrates were determined and analysed separately. The average proximate analysis of anthesising male inflorescence of oil palm recorded a high moisture content of 75%, followed by carbohydrate, protein, fat and ash. The amino acid profile revealed the presence of 18 amino acids with lysine having the highest content. The spikelet also recorded a total of 32 fatty acids with oleic acid recording the highest value. Nevertheless, the carbohydrate profile was not determined as its presence was in trace amount only. This study provided new knowledge and reference standard on the nutritional composition of anthesising male inflorescence of oil palm that is essential for E. kamerunicus.